A systematic review of types and efficacy of online interventions for cancer patients. Issue 3 (March 2015) - McAlpine, Heidi; Joubert, Lynette; Martin-Sanchez, Fernando; Merolli, Mark; Drummond, Katharine J.
Highlights This review critically examines efficacy of online interventions for cancer patients. Many online interventions are reported, however few are rigorously evaluated. Mixed results indicate the overall benefit of online interventions is unclear. Further study will improve understanding and development of online interventions.